002. Case Report: High Jejunal Atresia Type 1 Treated by Side to Side Anastomosis Jejuno-Jejunostomy - Zisnanda, Wildan Kharisma; Balela, Naisya; Poerwasusanta, Hery; Andayani, Pudji (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p002, 2024)
Background : Jejunal atresia characterized by complete occlusion lumen of the intestinal, is a rare congenital abnormality occurring in 1 out of 12.000 live births. The most recent hypothesis is that it caused by vascular accidents in the uterus during embryonic development. jejunal atresia Type I is characterized by mucosal, stenosis of the intestine. Some literature explains that side to side anastomosis surgery cannot be used in cases of jejunal atresia. The purpose of this case report is to present a case of high jejunal atresia type 1 managed with side to side anastomosis. Case: A 6 days old female with abdominal distension and billous vomiting since birth. the babygrams obtained a triple bubble sign. On emergency exploratory laparotomy, jejunum atresia was found 5 cm from the treitz ligament, no mesenteric defect, a web was found, the ratio of the diameter of the proximal and distal jejunum lumen was 7:1. The patient was decided to do Kimura procedure. The remaining bowel was normal.  We initiated enteral feeding on day 7 post operatively and then achieve full enteral feeding on day 25. Patient discharged without complication. Conclusion: High jejunal atresia type 1 can be managed with side to side anastomosis (jejuno-jejunostomy) surgery technique and the outcome was good.